Performance Analysis Of Guest Service Agent In The Front Office Department At The Westin Resort & Spa Ubud, Bali - Puspitasari, Kd. Ayu Sukma; Aryana, I Nyoman Rajin; Bagiastuti, Ni Ketut (Politeknik Sahid, 2022)
Purpose: The purposes of this research were to found out the performance of Guest Service Agent (GSA) in Front Office Department at The Westin Resort & Spa Ubud, Bali, and to find out the most significant indicators that affect the performance of Guest Service Agent in Front Office Department at The Westin Resort & Spa Ubud, Bali.Methods: The data collection methods used were literature studies, observations, observation sheets, and interviews. The data analysis techniques used were qualitative descriptive data analysis techniques.Results and discussion: The results of the research on the Observation Sheet Hourly Performance Process Form and interviews showed that the overall performance of the Guest Service Agent (GSA) at The Westin Resort & Spa Ubud, Bali, was considered reasonable by the superiors of Guest Service Agent (GSA), and has met the expected standards but requires continuous supervision and direction. Indicators rated Strong Performance (SP), including Problem Solving and Decision Making, Adaptability/Stress Tolerance, Time Management, Communication, and Customer Relations.Implication: The indicators assessed Key Contributor (K), which includes indicators Contributing to teams and Professional Demeanor. One of the seven indicators considered the most influential to the performance of Guest Service Agents was the Contributing to Teams indicator.